Danazol mediates collateral sensitivity via STAT3/Myc related pathway in multidrug-resistant cancer cells - Ying-Tzu Chang (Nature Portfolio, 2019)
Abstract Multidrug resistance presents an obstacle in cancer treatment. Among numerous combative strategies, collateral sensitivity (CS) drugs have opened a new avenue to defeat cancer by exploiting selective toxicity against multidrug-resistant (MDR) cancer. In the present study, a clinically used synthetic steroid hormone, danazol, was investigated for its CS properties and cytotoxic mechanisms. Compared with natural hormones, danazol possessed a stronger selective cytotoxicity against MDR cancer cells. Danazol induced the arrest of MDR cancer cells at the G2/M phase and caspase-8–related early apoptosis. Furthermore, in MDR cancer cells, danazol reduced STAT3 phosphorylation as well as the expression of STAT3-regulated genes involved in cell survival, such as c-Myc, CDC25, and CDK1. Danazol also upregulated the cell cycle inhibitor p21 in MDR cancer cells. Supporting the experimental results, docking studies have revealed that danazol can likely bind favourably with STAT3. Taken together, our results suggest that danazol exerts a CS effect by inhibiting the STAT3 pathway in MDR cancer cells and thus provides a possible solution for MDR cancers.